Visualization of brain microvasculature and blood flow in vivo: Feasibility study using confocal laser endomicroscopy. (8th February 2021) - Belykh, Evgenii; Zhao, Xiaochun; Ngo, Brandon; Farhadi, Dara S.; Kindelin, Adam; Ahmad, Saif; Martirosyan, Nikolay L.; Lawton, Michael T.; Preul, Mark C.
Abstract: Objective: Qualitative and quantitative analyses of blood flow in normal and pathologic brain and spinal cord microvasculature were performed using confocal laser endomicroscopy (CLE). Methods: Blood flow in cortical, dural, and spinal cord microvasculature was assessed in vivo in swine. We assessed microvasculature under normal conditions and after vessel occlusion, brain injury due to cold or surgical trauma, and cardiac arrest. Tumor‐associated microvasculature was assessed in vivo and ex vivo in 20 patients with gliomas. Results: We observed erythrocyte flow in vessels 5‐500 µm in diameter. Thrombosis, flow arrest and redistribution, flow velocity changes, agglutination, and cells rolling were assessed in normal and injured brain tissue. Microvasculature in in vivo CLE images of gliomas was classified as normal in 68% and abnormal in 32% of vessels on the basis of morphological appearance. Dural lymphatic channels were discriminated from blood vessels. Microvasculature CLE imaging was possible for up to 30 minutes after a 1 mg/kg intravenous dose of fluorescein. Conclusions: CLE imaging allows assessment of cerebral and tumor microvasculature and blood flow alterations with subcellular resolution intraoperative imaging demonstrating precise details of real‐time cell movements. Research and clinical scenarios may benefit from this novel intraoperative in vivo microscopic fluorescence imaging modality.